PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KINERJA LINGKUNGAN TERHADAP CARBON EMISSION DISCLOSURE DI INDONESIA: Studi kasus pada perusahaan manufaktur yang terdaftar di bursa efek indonesia - Julianti, Ni Ketut Trisna; Dewi, Putu Pande R. Aprilyani; Sunarta, I Nyoman; Arlita, I G A Desy (LPPM Universitas Bina Bangsa, 2025)
The rise in carbon emissions brought on by business operations that generate gasses that cause carbon emissions serves as the foundation for this study. This study seeks to assess the impact of profitability, firm size, and environmental performance on carbon emission disclosure in Indonesia, using a population of 165 manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sample used was 37 manufacturing companies so that 148 research data were obtained. The used analytical method was panel data regression analysis, using Eviews 12 software for data processing. The findings of this study demonstrate that profitability, company size, and environmental performance each exert a positive influence on carbon emission disclosure. Collectively, these variables account for 89.83% of the impact on carbon emission disclosure, with the remaining influence attributed to other factors. This study to serve as a reference for enhancing carbon emission disclosure in Indonesia, therefore facilitating the reduction and management of carbon emissions in the future. Keywords: carbon emission disclosure, profitability, company size, environmental performance